Bacterial coinfections in hospitalized children with COVID-19 during the SARS-CoV-2 Omicron BA.2 variant pandemic in Taiwan - Lai, Huan-Cheng; Hsu, Yu-Lung; Lin, Chien-Heng; Wei, Hsiu-Mei; Chen, Jiun-An; Low, Yan-Yi; Chiu, Yu-Ting; Lin, Hsiao-Chuan; Hwang, Kao-Pin (Frontiers in Medicine, 2023)
Background Bacterial coinfections have been widely recognized in adults with coronavirus disease 2019 (COVID-19). However, bacterial coinfections in hospitalized children with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have not been sufficiently researched. This study aimed to determine the clinical presentations and risk factors for bacterial coinfections of pediatric inpatients during the SARS-CoV-2 Omicron BA.2 variant pandemic. Methods This retrospective, observational study included patients younger than 18 years of age who were hospitalized for COVID-19 confirmed by polymerase chain reaction (PCR) or antigen rapid tests during the SARS-CoV-2 Omicron BA.2 variant pandemic. Data and outcomes of these patients with or without bacterial coinfections were compared. Results During this study period, 161 children with confirmed COVID-19 were hospitalized. Twenty-four had bacterial coinfections. The most frequently reported concurrent diagnosis was bacterial enteritis, followed by lower respiratory tract infections. Children with bacterial coinfections had higher white blood cell (WBC) counts and PCR cycle threshold values. The bacterial coinfection group comprised a relatively greater proportion of patients who required high-flow nasal cannula oxygen and remdesivir. The length of stay in the hospital and that in the intensive care unit were longer for children with COVID-19 with bacterial coinfections. Mortality was not observed in either group. Abdominal pain, diarrhea, and comorbidity with neurologic illnesses were risk factors for bacterial coinfections with COVID-19. Conclusion This study provides clinicians with reference points for the detection of COVID-19 in children and its possible association with bacterial infections. Children with COVID-19 and neurologic diseases who present with abdominal pain or diarrhea are at risk of bacterial coinfections. Prolonged fever duration and higher PCR test cycle threshold values, WBC levels, and high-sensitivity C-reactive protein (hsCRP) levels may indicate bacterial coinfections in children with COVID-19.